Voltage-Sensitive K+ Channels Inhibit Parasympathetic Ganglion Transmission and Vagal Control of Heart Rate in Hypertensive Rats - Berg, Torill (Frontiers in Neurology, 2015)
Parasympathetic withdrawal plays an important role in the autonomic dysfunctions in hypertension. Since hyperpolarizing, voltage-sensitive K+ channels (KV) hamper transmitter release, elevated KV-activity may explain the disturbed vagal control of heart rate (HR) in hypertension. Here, the KV inhibitor 3,4-diaminopyridine was used to demonstrate the impact of KV on autonomic HR control. Cardiac output and HR were recorded by a flow probe on the ascending aorta in anesthetized, normotensive (WKY) and hypertensive (SHR) rats, and blood pressure by a femoral artery catheter. 3,4-diaminopyridine induced an initial bradycardia, which was greater in SHR than in WKY, followed by sustained tachycardia in both strains. The initial bradycardia was eliminated by acetylcholine synthesis inhibitor (hemicholinium-3) and nicotinic receptor antagonist/ganglion blocker (hexamethonium), and reversed to tachycardia by muscarinic receptor antagonist (atropine). The latter was abolished by sympatho-inhibition (reserpine). Reserpine also eliminated the late, 3,4-diaminopyridine-induced tachycardia in WKY, but induced a sustained atropine-sensitive bradycardia in SHR. Inhibition of the parasympathetic component with hemicholinium-3, hexamethonium or atropine enhanced the late tachycardia in SHR, whereas hexamethonium reduced the tachycardia in WKY. Conclusions: 3,4-diaminopyridine induced acetylcholine release and thus enhanced parasympathetic ganglion transmission, with subsequent muscarinic receptor-activation and bradycardia. 3,4-diaminopyridine also activated tachycardia, initially by enhancing sympathetic ganglion transmission, subsequently by activation of norepinephrine release from sympathetic nerve terminals. The 3,4-diaminopyridine-induced parasympathetic activation was stronger and more sustained in SHR, demonstrating an enhanced inhibitory control of KV on parasympathetic ganglion transmission. This enhanced KV-activity may explain the dysfunctional vagal HR-control in SHR.